Les gestionnaires des espaces à caractère de nature face à l’évolution du climat urbain - Brice Dacheux-Auziere; Anne Marchand (Projets de Paysage)
This article examines the crucial role played by managers of urban nature spaces in the greening of urban environments in the context of climate change. An exploratory survey conducted among members of the Hortis association sought to understand the perceptions and actions of these managers in the face of climate change. Using a questionnaire and participant observations, the study analysed four main aspects : the management of urban nature spaces, urban greening, the use of plants, and urban planning. The findings revealed obstacles linked to the competence of managers, administrative structures and political constraints that limited the capacity to mitigate the effects of climate change. Differentiated management is emerging as an essential ecological approach in addressing the challenges of climate change but there remain obstacles such as the lack of human and financial resources and the lack of expertise and support from citizens and administrations. Adapting plant selections to local climatic conditions is also a challenge for managers faced with scientific uncertainties and a lack of experimentation and feedback. Urban planning appears to be a key tool for preserving urban nature spaces in cities. However, administrative complexity and political differences sometimes stand in the way of well-intentioned initiatives for the preservation of urban ecosystems. Nevertheless, green space managers are key players in the adaptation of urban landscapes. Their role as observers and guides of ecological transformations is crucial but they need improved resources and access to more popularised scientific knowledge to better integrate these practices to address climate change.